Multiallelic copy number variation in the complement component 4A (C4A) gene is associated with late-stage age-related macular degeneration (AMD). Issue 1 (December 2016) - Grassmann, Felix; Cantsilieris, Stuart; Schulz-Kuhnt, Anja-Sabrina; White, Stefan; Richardson, Andrea; Hewitt, Alex; Vote, Brendan; Schmied, Denise; Guymer, Robyn; Weber, Bernhard; Baird, Paul
Abstract Background Age-related macular degeneration (AMD) is the leading cause of vision loss in Western societies with a strong genetic component. Candidate gene studies as well as genome-wide association studies strongly implicated genetic variations in complement genes to be involved in disease risk. So far, no association of AMD with complement component 4 (C4 ) was reported probably due to the complex nature of theC4 locus on chromosome 6. Methods We used multiplex ligation-dependent probe amplification (MLPA) to determine the copy number of theC4 gene as well as of both relevant isoforms, C4A andC4B, and assessed their association with AMD using logistic regression models. Results Here, we report on the analysis of 2645 individuals (1536 probands and 1109 unaffected controls), across three different centers, for multiallelic copy number variation (CNV) at theC4 locus. We find strong statistical significance for association of increased copy number ofC4A (OR 0.81 (0.73; 0.89);P  = 4.4 × 10−5 ), with the effect most pronounced in individuals over 78 years (OR 0.67 (0.55; 0.81)) and females (OR 0.77 (0.68; 0.87)). Furthermore, this association is independent of known AMD-associated risk variants in the nearbyCFB/C2 locus, particularly in females and in individuals over 78 years. Conclusions Our data strengthen the notion that complement dysregulation plays a crucial role in AMD etiology, an important finding for early intervention strategies and future therapeutics. In addition, for the first time, we provide evidence that multiallelic CNVs are associated with AMD pathology.